MECHANISM OF OXYGEN REDUCTION REACTION ACTIVITY ON MANGAN-NIKEL DUAL-ATOM ELECTROCATALYST ACTIVE SITES LOCATED AT GRAPHENE NANOPORE EDGES FOR HYDROGEN FUEL CELL CATHODE APPLICATIONS - Helmi, Faizal
Graphene-based catalysts (M-N-C) have emerged as an alternative to platinum catalysts in fuel cell cathodes due to their low cost and abundant availability. Among the graphene-based catalysts under investigation, the Mangan-Nikel dual-atom catalyst (DAC) shows potential as an alternative due to its good activity and stability. This study focuses on exploring and analyzing the oxygen reduction reaction (ORR) activity of the MnNiN6 catalyst by introducing nanopores so that the active sites are at the edge of graphene. This research uses density functional theory (DFT), the computational hydrogen electrode (CHE) approach, and microkinetic modeling, this research examines surface structure stability, ORR thermodynamics, and ORR kinetics for the MnNiN6 catalyst. The results show that the presence of nanopores can facilitate the formation of active sites, which is indicated by lower formation energy values compared to active sites in the base. The thermodynamic and kinetic analyses of the ORR on the MnNiN6 catalyst show consistent results. In the ortho configuration, the active site located on the edge of graphene with armchair type (MnNiN6)o@a1 shows an increase in ORR activity by 0.17 V compared to the basal configuration. Meanwhile, the para configuration shows an endergonic reaction at the OH* intermediate stage; nevertheless, the para surface with an OH*-poisoned active site demonstrates a high onset potential in configutarion (MnNiN6_OH)o@z1 reaching 0.53 V, an increase of 0.12 V from the basal site. These findings indicate that the presence of nanopores in graphene can enhance the ORR activity of the MnNiN6 catalyst in specific configurations. Keywords: Dual-Atom Catalyst (DAC), MnNiN6, DFT, ORR, fuel cell.